Biomass ashes from agricultural wastes as supplementary cementitious materials or aggregate replacement in cement/geopolymer concrete: A comprehensive review. (August 2021) - Thomas, Blessen Skariah; Yang, Jian; Mo, Kim Hung; Abdalla, Jamal A.; Hawileh, Rami A.; Ariyachandra, Erandi
Abstract: This paper aims to provide a comprehensive review of recent trends in incorporating biomass ashes from agricultural waste in Ordinary Portland cement (OPC) and geopolymer concrete. The material properties of different biomass ashes and their effect on fresh and hardened concrete properties (i.e., mechanical and durability properties) are reviewed. Partial replacement of OPC with byproducts, such as bamboo leaf ash, date palm ash, elephant leaf ash, banana leaf ash and plantain peel ash, rice straw ash, olive waste ash, wheat straw ash, and corn cob ash, escorts reduction in carbon dioxide (CO2 ) emissions and global warming. It will also contribute to the effort of achieving zero-waste technology and sustainable development. This paper provides essential background information on the global status, composition, and ash preparation procedures of green and sustainable cementitious materials and then explores their potential applications. This review also highlights the areas requiring further research and indicates the possible negative impacts of utilizing these non-traditional supplementary cementitious materials (SCMs). The findings from this review confirm the feasibility of using biomass ashes as pozzolanic materials in cement concrete or as alternative activators in geopolymer concrete, with the required properties of building materials. Also, it is expected that this review will provide a better insight into biomass ashes incorporated in concrete for the benefit of academic/fundamental research and the construction industry. Highlights: Reviews the utilization of agricultural farming waste ashes as SCMs. 100 literatures were extensively reviewed. Essential information including global status, composition and preparation procedures. Explores the potential application as a green and sustainable cementitious material. Findings confirmed the feasibility of biomass ashes in cement/geopolymer concrete.